Asian catfish Clarias batrachus (Linnaeaus, 1758) getting critically endangered. - Argungu, L. A; Christianus, Annie; Nurul Amin, S. M; Daud, Siti Khalijah; Siraj, Siti Shapor; Rahman, Md. Aminur (Academic Journals Inc, 2013)
The presence of Asian catfish, Clarias batrachus in Malaysia is at a deteriorating state. It is hardly a cultured species since the supply of seed is unavailable. This species is found in lowland streams, swamp and rice fields. Therefore, they are greatly exposed to factors such as intermittent periods of drought, devastation of the natural habitat and agro-chemicals. Presently, fish farmers are more into the culture of Clarias gariepinus. This threatened the mere existence of this indigenous C. batrachus. Hardiness, good growth, efficient food conversion and excellent nutritional profile guarantee C. batrachus as a suitable aquaculture candidate. Some conservation efforts were looked into in order to prevent the extinction of this potentially important catfish.